How Far Does Cognitive Depletion Impact Cinderella Shopping? Mediation Through Hedonic and Utilitarian Value Perceptions - V. M., Jasmine; Jose, Nithin; V. N., Sruthiya (Indian Journal of Marketing, 2024)
Purpose : The present study examined the online midnight time-bounded shopping habit, the Cinderella shopping behavior. This growing trend among online consumers, followed by sales promotional offers, induced us to discover the direct effects of cognitive depletion on hedonic value perception, utilitarian value perception, and attitude, leading to the Cinderella shopping habit. Moreover, we tried to measure the indirect effect of cognitive depletion on attitude mediated through hedonic and utilitarian value perceptions. Design/Methodology/Approach : This empirical research undertook four independent latent variables, namely cognitive depletion, hedonic value perception, utilitarian value perception, and attitude, and one dependent variableâ€”â€œCinderella Shopping Habit.â€ For the study, we applied purposive sampling, floated a structured questionnaire, received 400 responses, and ran the analysis on Jamovi software. Findings : We found that cognitive deletion has a significant positive influence on hedonic value perception, utilitarian value perception, and attitude. Similarly, hedonic and utilitarian value perceptions showed a significant partial mediation effect in the relationship between cognitive depletion and attitude. Finally, the attitude framed on the above constructs impacted the Cinderella shopping habit. Practical Implications : It is recommended that marketers and webpreneurs utilize the new movement in online shopping behavior wisely, considering the variables identified here. Though our study has its limitations, it allows scope for future researchersâ€”variations in the effect of cognitive depletion on late-night shopping among consumers of different categories and products can be studied in the future. Originality/Value : Unlike prior research, the current work builds a model to examine midnight timebounded online consumer behavior by focusing on cognitive depletion.